Aplikasi Mudah Alih Belajar Arah dan Kedudukan: Geo Arah - MOHAMMAD ASRI, MUHAMMAD AIMAN BIN; NORHANIFAH MURLI (Applied Information Technology And Computer Science, 2024)
Geography is one of the subjects studied in high school. Among the topics taught is about direction and position. However, the lack of Teaching Aids for teachers causes students to depend entirely on the medium of learning through textbooks. Therefore, the Geo Arah application is developed for Android mobile phones by applying 2- dimensional techniques. This application is developed using Unity software and the target users of this application is produced using the Multimedia Mobile Content Development (MMCD) methodology. The content and modules in this application are referenced from the Subject Matter Expert (SME) and Form 4 Geography textbooks to obtain accurate information. This application is expected to help Form 4 students to learn the topic of direction and position in an interactive and fun way so that what is learned is easy to understand and memorise